2008
DOI: 10.1021/jp7099477
|View full text |Cite
|
Sign up to set email alerts
|

On the Nonsingle-Site Character of Bis(2-Dimethylsilyl-indenyl)zirconium(IV) Dichloride/MAO and Bis(2-Trimethylsilyl-indenyl)zirconium(IV) Dichloride/MAO:  Polymerization Characteristics and Mechanistic Implications

Abstract: Ethene polymerization with bis(2-dimethylsilyl-indenyl)zirconium(IV) dichloride (1)/MAO and bis(2-trimethylsilyl-indenyl)zirconium(IV) dichloride (2)/MAO and ethene-co-1-hexene polymerization with 1/MAO are presented. The end group analysis of homopolymers reveals a pronounced dependence of the termination rate on temperature changes. In combination with the high molecular weights obtained, these results are in accord with theoretical predictions. Gel permeation chromatography, Fourier transform infrared, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…GPC analysis of the polyethylenes produced with benzothiazole based complexes revealed that the symmetric catalysts systems were capable to produce resins with very high molecular weights [28,29] associated with broad or even bimodal molecular weight distributions (Fig. 13).…”
Section: Polymerization Resultsmentioning
confidence: 99%
“…GPC analysis of the polyethylenes produced with benzothiazole based complexes revealed that the symmetric catalysts systems were capable to produce resins with very high molecular weights [28,29] associated with broad or even bimodal molecular weight distributions (Fig. 13).…”
Section: Polymerization Resultsmentioning
confidence: 99%
“…At 40 °C (Scheme 16) a polyolefin with M w = 1.2·10 6 g/mol and PDI = 248 was obtained.Increasing the polymerization temperature to 60 °C (Scheme 17) both molecular weight (M w = 9.7·10 5 g/mol) and PDI = 223 decreased. The high molecular weight resins and the decrease of molecular weight with increasing polymerization temperature suggest that the rate of propagation reactions (the activation barrier for propagation is usually low if existent at all)[41,42] are much faster than the rate of termination (the termination reactions are subjected to activation barriers).Scheme 16. HT-GPC profile of polyethylene produced with 29/MAO at 40 °C.…”
mentioning
confidence: 99%